Application of ferrofluids for enhanced oil recovery: Impact on heavy and light oils in heterogeneous and homogeneous micromodels - Milad Khashay; Tarek Ganat; Ehsan Esmaeilnezhad (Results in Engineering)
Enhanced oil recovery (EOR) techniques play a crucial role in increasing hydrocarbon production from mature reservoirs, particularly in light and heavy oil systems. This study explores the potential of synthesized citric acid-coated magnetite (Fe3O4) nanoparticles (CM NPs) as a novel, cost-effective, and environmentally friendly EOR agent. The synthesized CM NPs were characterized using field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), and Fourier transform infrared spectroscopy (FTIR) to confirm their structure, size distribution, stability, and functional groups. Their EOR performance was then evaluated in both homogeneous and heterogeneous two-dimensional micromodels and compared with conventional low-salinity water flooding (5000 ppm NaCl) and polymer (polyacrylamide) flooding. Image analysis revealed that in the heterogeneous heavy oil micromodel, CM NP-assisted flooding achieved a recovery factor (RF) of 66.02 %, which was higher than water flooding (59.04 %) but lower than polymer flooding (83.12 %). In the homogeneous light oil model, CM NPs achieved 80.89 % RF, surpassing water flooding (67.69 %) and approaching polymer flooding (86.36 %) performance. The improved oil recovery using CM NPs is attributed to their ability to reduce interfacial tension, alter wettability, and slightly increase displacing fluid viscosity. Additionally, their magnetic properties allow for easy post-recovery separation, enhancing environmental sustainability and reusability. These findings demonstrate that CM NPs offer a promising alternative to traditional EOR methods, particularly in scenarios where polymer flooding may be less practical or economically viable.